Enhancing the Learning Environment through the Effective Classroom Management - Garaja, Khulya; Huseynova, Nargiz; Yolchuzada, Saadat (ADA University, 2022)
Managing or minimizing student disruptive behavior is one of the most important aspects for an effective teaching and learning process. For this reason, it is important to examine the methods that teachers use to prevent undesirable student behavior and whether these methods are effective. The aim of this study is to identify the most common disruptive student behaviors that teachers encounter in the classroom in schools and what strategies they use to address these behaviors. This project examines student disruptive behavior encountered by teachers at an International Baccalaureate (IB) school in Baku during class and the strategies used by teachers to manage those behaviors. In this study, 8 teachers were interviewed using semi-structured interview forms. Based on the results of the study, it was found that teachers noted students' behaviors such as starting off-topic discussions, inappropriate gadget use, starting disruptive noises, unrecognized / out-of-turn speaking, and so on. In addition, focus group interviews with 12 students who are studying at 8th and 9th grade were conducted to find out what disruptive behaviors they demonstrated in the classroom, whether they considered their manners disruptive, and how instructors managed these behaviors. According to our study, teachers stated that they use strategies such as keeping silence, clearly stating expectations and rules, private problem discussion, building empathy with students, and student-centered teaching for effective classroom management.
Keywords: Classroom management.; Disruptive behavior.; Management strategies.; Education